SISTEM PEMULIAAN INTI TERBUKA UPAYA PENINGKATAN MUTU GENETIK SAPI POTONG - Rikhanah Rikhanah (MEDIAGRO, 2008)
The influence of beef meat stock in Center Java is least increase on 2002-2006.  However beef meat supplier more doing in rural livestock with management and pure social condition itself. To supply necessity of red meat and  increasing productivity of beef cattle, cattle quality genetic correction  doing first because selection of cattle quality that care conclude management maintenance and the result of production. Book study method used in this paper. Genei breeding sysem like open nuleus breeding. There are two method of open nucleus breeding, first,  involve two group of breeder, nucleus herd breeder and village herd breeder under breeder cooperation management, second, involve three group of breeder, nucleus herd breeder, pre-nucleus  herd breeder and commercial herd breeder.  Implementation of government doing with integrity service pattern  in group in one service  pattern.   On cost, development of rural breeding doing with government services model and  partner model .Key words : open nucleus breeding, genetic quality, beef cattle